Structural requirements for anti-oxidant activity of calix[n]arenes and their associated anti-bacterial activity - Stephens, E.; Tauran, Y.; Coleman, A.; Fitzgerald, Melinda (The Royal Society of Chemistry, 2015)
Treatment of neural cells with calix[n]arenes featuring sulphonate moieties and linked to Ag nanoparticles results in reduced reactive species. For gram+ bacteria there is an inverse correlation between anti-bacterial activity and ROS reduction whereas for gram- bacteria only calix[6]arenes bearing O-alkyl sulphonate functions act as ROS inhibitors and anti-bacterial agents.